RISK FACTORS OF INFERTILITY AMONG INDONESIAN WOMEN: A CROSS-SECTIONAL STUDY - Septiana, Lisa; Pakki, Irfansyah Baharuddin (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2025)
Background: Infertility affects approximately 10-15% of couples in Indonesia and 48.5 million couples globally. It is a growing public health concern that impacts women due to various biological, psychological, and environmental factors. The increasing rates of female infertility, influenced by unhealthy lifestyles, emphasize the critical need for effective treatments and interventions for infertility. Purpose: This study aims to determine the relationship between risk factors such as age, BMI, employment status of wife and husband, and menarche age with infertility. Methods: This cross-sectional study was conducted at Rizafa Clinic in 2023, involving a purposive sample of 150 women. Variables such as age, obesity (determined by BMI), age at menarche, and occupation were both analyzed, and a chi-square test was performed to assess the association between risk factors and infertility. Results: The study revealed that female infertility is significantly influenced by obesity (p = 0.001). However, there was no association between age (p = 0.150), women’s occupation (p = 0,310), husband's occupation (p = 0,233), and menarche age (p = 0,969) with infertility. Conclusion: It can be concluded that there is a correlation between obesity and the incidence of infertility. Lifestyle changes that support reproductive health in women include maintaining a healthy body weight as a foundation and limiting the intake of foods high in sugar, saturated fats, and processed ingredients, as these can negatively impact metabolism and hormone balance. Addressing these key risk factors through lifestyle adjustments is essential for improving fertility outcomes.